2023
DOI: 10.1096/fj.202300488r
|View full text |Cite
|
Sign up to set email alerts
|

Hmga1‐overexpressing lentivirus protects against osteoporosis by activating the Wnt/β‐catenin pathway in the osteogenic differentiation of BMSCs

Abstract: Postmenopausal osteoporosis is associated with bone formation inhibition mediated by the impaired osteogenic differentiation potential of bone marrow mesenchymal stem cells (BMSCs). However, identifying and confirming the essential genes in the osteogenic differentiation of BMSCs and osteoporosis remain challenging. The study aimed at revealing the key gene that regulated osteogenic differentiation of BMSCs and led to osteoporosis, thus exploring its therapeutic effect in osteoporosis. In the present study, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In this experiment, lentiviral vectors carrying target genes were chosen to transfer into BMSCs, taking into account the growth characteristics and survival time of BMSCs. The lentivirus showed the highest activity between 72 and 120 h after being introduced into BMSCs, aligning with the expected transfection properties of lentivirus [ 20 , 21 ]. Thus, our group decided to measure gene expression 72 h post-transfection.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, lentiviral vectors carrying target genes were chosen to transfer into BMSCs, taking into account the growth characteristics and survival time of BMSCs. The lentivirus showed the highest activity between 72 and 120 h after being introduced into BMSCs, aligning with the expected transfection properties of lentivirus [ 20 , 21 ]. Thus, our group decided to measure gene expression 72 h post-transfection.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro experiments showed that HMGA1 expression increases during osteogenesis of rat BMSCs and decreases during ovariectomy. Bone loss during ovariectomy in rats was compensated by the introduction of a lentivirus inserting HMGA1 into the bone marrow cavity; therefore, HMGA1 is considered a potential gene therapy target for the treatment of osteoporosis [182]. The clinical potential of the adeno-associated virus, an inhibitor of the WNT/β-catenin signaling pathway antagonists SHN3 and SOST, was demonstrated in terms of enhanced osteoblast function and bone formation [183].…”
Section: Promising Directions Of Osteoporosis-targeting Therapymentioning
confidence: 99%
“…OPG (osteoprotegerin) is a natural antagonist of RANKL, which can bind to RANKL and prevent it from binding with RANKL, thus inhibiting bone resorption 6 . Activating the Wnt/β- catenin pathway can promote the proliferation and differentiation of osteoblasts and increase bone formation 7 , 8 . Estrogen can inhibit bone resorption by reducing the formation of osteoclasts and prolonging their life span, and can also promote the activity of osteoblasts 9 .…”
Section: Introductionmentioning
confidence: 99%